Contrast-induced nephropathy: A contemporary and simplified review - (:unkn) unknown (My University, 2010)
Contrast-induced nephropathy (CIN) is the third most common reason for hospital-acquired acute kidney injury. In-hospital and long-term mortality and morbidity (e.g., stroke, myocardial infarction and vessel re-occlusion) incidences are higher in patients who develop CIN as opposed to patients without CIN. Evolving diagnostic and interventional procedures make CIN a more serious problem than it was previously. Accordingly, efforts to reduce CIN incidence have received particular attention in recent years, and many studies have been published regarding this issue. In this article, we conduct a systematic literature search of the most recent evidence available from 2000 to 2010, with the purpose of providing practical suggestions for prevention of CIN. © 2010 Future Medicine Ltd.
Keywords: contrast agent; contrast-induced nephropathy; interventional cardiology